Eficiência técnica do gasto público em educação: uma análise empírica para os municípios cearenses no período de 2007 a 2017 face aos resultados do IDEB - Santiago, Moisés Chaves (2019)
This paper analyzed the technical efficiency of public spending on education in the municipalities of the state of Ceará, from 2007 to 2018, against the results of the Basic Education Development Index (IDEB). In search of the factors that, in fact, most influence educational performance and using the IDEB as a result indicator, a comprehensive database was constructed, containing 414 variables, including infrastructure-related inputs, teacher profile, enrollment, student achievement and characteristics of municipalities. The sources used were the Secretary of Education of the State of Ceará (SEDUC), the National Treasury Secretariat (STN) and the Anísio Teixeira National Institute for Educational Studies and Research (INEP). The analysis was performed using the stochastic frontier econometric model estimated by the maximum likelihood method for a Cobb-Douglas production function. From the resulting model, it was concluded that the percentage of municipal public school teachers in elementary school with higher education, the percentage of municipal public schools with computer lab, the approval rate of municipal public school students, the age-grade distortion in elementary school and the number of schools with library for reading influence the result of high IDEB. Regarding the number of enrollments in elementary school, although not statistically significant, its influence on INEB is suspected. Also, according to the technical efficiency scores resulting from the model, the municipalities of Jijoca de Jericoacoara, Russas and Icapuí stood out as the most efficient.